Rois dalam Pendidikan Karakter Umat - Siti Afifah Adawiyah (Islamic University of Indonesia, 2019)
Character education is still a focus in today's national educational objectives. School is no longer the only part that should transfer character education but also to family and society. These three sections should be synergized to realize character education. If in school is a teacher's assignment, then in society is the task of Rois as a religious leader in his region. With a qualitative approach, data is collected using interview and observation techniques. The results showed that the factors influencing the success of Rois in internalizing the Islamic character of the community are customary or habitual, wills or willpower, descent, and education. Furthermore, in carrying out the role of a religious leader in a region, Rois experienced a change in himself namely the change of Rois’ behavior, religious scholarly mastery, and dedication of time and energy.